2007
DOI: 10.1557/jmr.2007.0145
|View full text |Cite
|
Sign up to set email alerts
|

Reliability analysis of Au–Sn flip-chip solder bump fabricated by co-electroplating

Abstract: In this study, we fabricated eutectic Au–Sn (Au–20 wt% Sn) flip-chip solder bumps from a single electroplating bath. After reflowing, the average diameter of the solder bump was approximately 80 μm. The (Ni,Au)3Sn2 phase was initially formed when the liquid Au–Sn solder reacted with the Ni UBM (under bump metallization). After aging at 150 °C, the (Ni,Au)3Sn2 intermetallic compound (IMC), which formed at the interface during reflow, was fully transformed into the (Au,Ni)Sn IMC due to the restricted supply of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…6(a)) was consumed and -phase covered the (Au,Ni)Sn IMC layer, indicating that the Ni(P) substrate reacted primarily with the ␦-phase rather than the -phase in the solder. A similar result was also reported in the literature [6,21]. On the other hand, we recently studied the interfacial reactions of Au-20Sn/Cu solder joint [22], and reported that the Cu substrate reacted primarily with the -phase in the solder.…”
Section: Solid-state Interfacial Reactionsupporting
confidence: 88%
See 1 more Smart Citation
“…6(a)) was consumed and -phase covered the (Au,Ni)Sn IMC layer, indicating that the Ni(P) substrate reacted primarily with the ␦-phase rather than the -phase in the solder. A similar result was also reported in the literature [6,21]. On the other hand, we recently studied the interfacial reactions of Au-20Sn/Cu solder joint [22], and reported that the Cu substrate reacted primarily with the -phase in the solder.…”
Section: Solid-state Interfacial Reactionsupporting
confidence: 88%
“…Eutectic Au-20Sn (in wt.%) solder has been widely used for bonding applications in microelectronic and optoelectronic packages because it can provide relatively low melting point, high strength, low elastic modulus and high thermal conductivity [1][2][3][4][5][6][7][8][9][10][11]. The Au-Sn binary system has a complicated equilibrium phase diagram, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the diffusion and reaction of metallic atoms are accelerated under the combined loading of high temperature, moisture, and pressure. Therefore the fractures are formed along the interface or through the bulk of the solder with the growth of the brittle inter-metallic compound layers, such as (Au, Ni)Sn and (Ni, Au) 3 Sn 2 [25]. However, the average shear strength after the combination test was still satisfied the MIL-STD-883F specification.…”
Section: B Reliability Testmentioning
confidence: 99%
“…The material stress-strain properties and material lifetime S-N dependence (i.e. cyclic stress vs. cycles to failure) corresponding to the metallic materials have been taken from [5][6][7]. The initial stress has been determined, as in Section 4.1, according to the temperature profiles imposed during soldering and moulding processes.…”
Section: Led Board Lifetimementioning
confidence: 99%